Improving the innovative work - Sundell, Melissa; Hormez, Aiad (My University, 2020)
The notion of innovation management is well studied within literature and the importance of being innovative is frequently discussed among firms. Being innovative is crucial for a company's survival and to sustain profitable. Furthermore, in order to become innovative, the firm need to innovate for its existing business as well as for future activities. In this project, a company’s ability to innovate has been investigated. More accurately, how they can improve their radical innovation. The research has had the purpose of conducting how the studied Company can be organised in order to generate radical innovations while maintaining their ability of incremental innovation. To answer the research question, a case study has been executed at the firm, defined as Company C. The methodology used is based on empirical research of an explorative approach. This in order to gain an in-depth understanding of the situation in combination with knowledge from literature and comparison with other organisations in similar situation. The procedure was initiated by defining the problem at Company C, followed by an investigation of the problem area. The investigation included a literature review and a comprehensive understanding on the studied organisation. Once a more thorough view of the problem area was concluded, a re-definition of the problem was made. Last, ideation of possible improvements took place, with the most suitable suggestion presented to the supervisors. After each phase, the delivered outcome has been discussed with supervisor from Company C. It was found that Company C is a growing firm with a great foundation of ambitious employees. The cultural environment within the organisation fosters innovation and the employees are comfortable with changes. Employees perceives the company as innovative and that they manage incremental innovation with excellence. However, they do believe the organisation is lacking capabilities to innovate radically. Their innovative process is theoretically built upon a three-step model which relies on creating a flow of ideas streaming from a design thinking procedure, that later evolves and transitions into the organisation. The understanding of how this innovative model is executed is perceived unclear among employees. It is found that the ideas generated from the design thinking procedure is struggling and that employees experience radical development to be difficult. Ideas should derive from customer insight, which may not always be in favour for radical exploration. Furthermore, in order to develop an idea, the one who got the idea need to promote it themselves internally and find external support. In conclusion, Company C has potential of improving their ability to innovate by further develop their level of ambidexterity into reaching dynamic ambidexterity. It is recommended that the organisation should include a divided responsibility with ambidextrous leadership for exploitation and exploration in its contradicting environments. For explorative projects where tasks of sensing the environment is executed, a visionary leadership is required. The manager should have strong participation in dialogs with the explorative units, described as “Innovation thinking team” and “Start-up incubation team” in the innovation model. The explorative unit should furthermore create a closer relationship with the sales department to obtain an increased overview of the market. For exploitative projects, where the ability to seize an opportunity is performed, a result-oriented leadership is more suitable. It is suggested that this unit should have a strong connection with the “Agile development team” and the manager need to support the transition into the ongoing business as described in the innovation model.
Keywords: Innovation management; Ambidexterity; Dynamic Ambidexterity; Ambidextrous leadership